Myringoplasty with temporalis fascia - Tawfique, Saleh A.; Alnakshabandi, Abdulla (Sulaimani Journal for Pure and Applied Sciences, 2012)
A retrospective study for myringoplasty operations at ENT department, Alain hospital, Alain city-UAE for the last 5 years (2004-2009) done. Total 64 patients with central tympanic membrane perforation were operated by one surgeon using Temporalis fascia graft for repair and using underlay technique. In 56 cases (87%) graft were taken completely while in 8 (13%) cases graft, were partially taken and patients had smaller residual perforation. 39 ears (60%) had normal hearing or improved hearing up to 15 dB air-bone gape. The average time for follow up was 37 months (2-72 months).
Keywords: Myringoplasty; Temporalis fascia graft